1992
DOI: 10.2307/3350216
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Cost of Health Services Prior to Death: A Comparison of the Medicare-Only and the Medicare-Medicaid Elderly Populations

Abstract: Lack of data has limited research into the high cost and ethical dilemmas associated with care of the dying elderly. This study is based on a five-year, person-specific file of Medicare and Medicaid use and cost data for residents of Monroe County, New York, over the age of 65. It examines and compares utilization and expenditure patterns of the Medicare-only and the Medicare-Medicaid (dually eligible) decedents in 1988. Examination of reimbursement for nonacute services, not covered by Medicare, reveals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 8 publications
3
27
0
Order By: Relevance
“…As with the cost changes related to proximity to death, this age-cost pattern was driven by changes in the probability of being in hospital, which increased to age 85 and fell thereafter. The decreasing probability of hospitalisation at the end of life in the oldest ages could be due in part to increasing use of long-term care facilities among older patients [15][16][17][18][19][20]. There could also Quarter to death Average quarterly cost (1998-99£) Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…As with the cost changes related to proximity to death, this age-cost pattern was driven by changes in the probability of being in hospital, which increased to age 85 and fell thereafter. The decreasing probability of hospitalisation at the end of life in the oldest ages could be due in part to increasing use of long-term care facilities among older patients [15][16][17][18][19][20]. There could also Quarter to death Average quarterly cost (1998-99£) Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that elderly people approaching death have very high utilization of and expenditures for medical care (36,65,66,72,73,82). In one of their earliest studies, Lubitz & Prihoda (36) found that in 1978 1.1 million Medicare enrollees were in their last year of life.…”
Section: Medical Expenditures In the Last Year Of Lifementioning
confidence: 99%
“…Several studies of the association between the demographic variables (age, gender and survival status) and health care expenditure have been carried out in the United States [7,11,18,21,[26][27][28][29], Germany [20], The Netherlands [30], Denmark [19,25], United Kingdom [16] and in British Columbia [31]. These studies demonstrate that the association between demographic variables and expenditure depends on type of health care service, whereas life long expenses due to acute care increase at a decreasing rate as age at death increases, nursing home expenses increase at an accelerated rate [21].…”
Section: Introductionmentioning
confidence: 99%